Spontaneous Erection and Masturbation in Mithun (Bos frontalis) Bulls - Perumal, P.; Vupru, K.; Khate, K.; Veeraselvam, M.; Verma, Atul Kumar; Nahak, A. K.; Rajkhowa, C. (International Journal of Bio-resource and Stress Management, 2023)
In domestic species, spontaneous erection and penile movements or manipulation occur in an awake state, the behaviour is commonly known as masturbation. Six mithun bulls were selected, of which, three from Mizoram and three from Manipur strain. These strains were observed over a period of 12 months. This behaviuor were observed from 1800 to 800 hrs and especially in winter and spring season. The parameters studied were duration of erection, frequency of movements of penis, time of sexual erection and masturbation. Seminal parameters such as volume, mass activity, progressive motility, live sperm, concentration, abnormality, acrosomal integrity and HOST were studied, which were collected by massage method. Other parameters such as success rate, protrusion time, length of penis and ejaculation time were also studied. The seminal parameters were showed that there was no significant difference between the affected and unaffected animal. But the unaffected animals were non-significantly higher in seminal parameter than affected animals.